Nutriments consumption of bulb onion plants under depending on methods of irrigation and chemical fertilizers - Куц, О. В.; Зелендін, Ю. Д.; Вітанов, О. Д. (Scientific Progress & Innovations, 2013)
Separate and local fertilization under drop irrigation promote reception of marketable yield of bulb onion on level 28.4–28.6 t/hа on the left-bank Forest Steppe of Ukraine. That elements of technology provide the highest activity of consumption by bulb onion plants out of fertilizers of nitrogen – 26–40 %, phosphorus – 4–6 %, potassium – 16–33 %. The removal of elements of nutrition increases with the increase of the level of crop yield. Under drip irrigation and localization of the application of fertilizers consumption elements of the nutrition supply at the formation of the units of the harvest is 3,08 kg/t of nitrogen, from 1.07 kg/t of phosphorous and total 1.74 kg/t of potassium.